ANALISIS DETERMINAN KREDIT MACET PADA UMKM DI INDONESIA - Hanif, Muhamad Shafwan; Widawati, Anik Sri (Jurnal Riset Entrepreneurship, 2024)
MSMEs play a vital role in boosting Indonesia's economy, and to enhance this sector, the government offers banking support for the allocation of MSME loans. Although the distribution of loans to MSMEs is increasing, there is a rising trend in the risk of non-performing loans. This risk stems from debtors' inability to meet their obligations with creditors due to various factors. This study aims to assess the impact of MSME credit growth, interest rates, MSME working capital credit, and MSME GDP on non-performing loans in Indonesia's MSMEs. Utilizing a quantitative approach and secondary data from Bank Indonesia, the Financial Services Authority, and the Central Statistics Agency, the research employs multiple linear regression through Eviews 10. The time series data spans from 2011 to 2022, and the findings reveal that each variable—MSME credit growth, interest rates, MSME working capital credit, and MSME GDP—significantly influences non-performing loans in Indonesia's MSMEs.